2015
DOI: 10.1590/1677-5449.01715
|View full text |Cite
|
Sign up to set email alerts
|

Estresse oxidativo e a função endotelial: efeitos do exercício físico associado à lipemia pós-prandial

Abstract: Resumo Estratégias que possam prevenir o aparecimento da aterosclerose são de extrema importância para a saúde pública. O aumento da lipemia pós-prandial tem sido investigado, dentre os fatores de risco modificáveis para o desenvolvimento dessa doença, pois pode induzir dano oxidativo e disfunção endotelial. Nesse sentido, o exercício físico é indicado na prevenção do desenvolvimento desses fatores de risco. Esta revisão tem como objetivo realizar um levantamento e comparar os estudos publicados na literatura … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 61 publications
0
4
0
1
Order By: Relevance
“…Platelet count and volume were not influenced by food intake of dogs, however, Pavlishchuk et al (2004) reported that after feeding there may be an increase in plasma fibrinogen that modulates the early stages of platelet aggregation and its interrelation with other cells in humans, thus contributing to increased platelet aggregation. Corroborating these findings, Krüger, Farinha, Teixeira and Oliveira (2015) indicate that this response is probably due to endothelial dysfunction caused after eating. Taken together, these factors could contribute to postprandial platelet consumption.…”
Section: Resultsmentioning
confidence: 53%
“…Platelet count and volume were not influenced by food intake of dogs, however, Pavlishchuk et al (2004) reported that after feeding there may be an increase in plasma fibrinogen that modulates the early stages of platelet aggregation and its interrelation with other cells in humans, thus contributing to increased platelet aggregation. Corroborating these findings, Krüger, Farinha, Teixeira and Oliveira (2015) indicate that this response is probably due to endothelial dysfunction caused after eating. Taken together, these factors could contribute to postprandial platelet consumption.…”
Section: Resultsmentioning
confidence: 53%
“…In this sense, previous studies have shown that exercise performed a few hours before the consumption of a HFM can attenuate oxidative damage and endothelial dysfunction induced by the meal (Bae et al 2001;Clegg et al 2007;Mc Clean et al 2007;Jenkins et al 2011;Krüger et al 2015). However, only few studies have investigated the effect of exercise intensity (Tyldum et al 2009;Gabriel et al 2012;Canale et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This increase in the serum TG concentration and a probable inefficiency in the removal of triglyceride-rich lipoproteins (LRTs) can increase the inflammatory process and intensify the increase of reactive species in the postprandial period, consequently leading to oxidative damage [44]. In the present study, the biomarker of inflammatory activity TNFα was evaluated, which is closely associated with low-grade inflammation, systemic oxidative stress and the formation of atherosclerotic plaque in obese and dyslipidemic individuals [45,46].…”
Section: Discussionmentioning
confidence: 95%